Complementing knowledge about rare sulphates lonecreekite, NH4Fe3+(SO4)2·12 H2O and sabieite, NH4Fe3+(SO4)2: chemical composition, XRD and RAMAN spectroscopy (Libusin near Kladno, the Czech Republic) - Zacek,V.; Skoda,R.; Laufek,F.; Kosek,F.; Jehlicka,J. (Journal of Geosciences, 2019)
Lonecreekite and sabieite, hydrous and anhydrous ferric ammonium sulphates, were identified among the products of a long-lasting subsurface fire in the waste heap of the Schoeller coal mine in Libusin near Kladno, Central Bohemia, Czech Republic. No monomineralic fractions could be extracted as the minerals occur in a fine-grained aggregate with minor ferroan boussingaultite, tschermigite, and traces of efremovite. Powder X-ray diffraction, electron-microprobe analysis and Raman spectroscopy were used to identify the mineral phases in the mixture. The empirical formula of lonecreekite is [(NH4)0.98K0.02]∑1.00 (Fe0.70Al0.24Mg0.02)∑0.96 (SO4) 2.05·12 H2O, and the calculated unit-cell (Pa ) parameter a = 12.2442(2) Å, with a cell volume of V = 1835.68(9) Å3. The composition of sabieite corresponds to the formula [(NH4)0.98K0.02]∑1.00 (Fe0.70Al0.24Mg0.02)∑0.96 (SO4) 2.05, and the calculated unit-cell parameters (P321) are a = 4.826(1) Å, c = 8.283(2) Å, V = 167.10(8) Å3, assuming that only the 1T polytype is present. Raman spectroscopy was conducted on both minerals, giving strong Raman bands at 1037 cm-1 (ν1), 1272 cm-1 (ν3), 462 cm-1 (ν2), 643 cm-1 (ν4), 313 (M-O vibration) for sabieite; and at 991 cm-1 (ν1), 1132 and 1104 cm-1 (ν3), 461 and 443 cm-1 (ν2), and 616 cm-1 (ν4) for lonecreekite (where ν1 and ν3 are stretching modes of the (SO4)-group and ν2 and ν4 are bending modes). The sabieite most probably formed by in situ decomposition of the siderite-bearing sedimentary rock at ˜115-350 °C. The lonecreekite originated through hydration of the sabieite when the sample was stored at ambient temperature. Empirical formulae of associated ferroan boussingaultite and tschermigite are also given, respectively, as (NH4)2 (Mg0.62Fe0.36Mn0.06)∑1.04 (SO4)1.97·6 H2O and [(NH4)0.98K0.02]∑1.00 (Al0.97Fe0.06)∑1.03 (SO4)2.97·12 H2O.
Keywords: sabieite; lonecreekite; Kladno; burning heaps; electron microprobe; Raman spectroscopy